Differential determination of perceived stress in medical students and high-school graduates due to private and training-related stressors - Erschens, Rebecca; Bugaj, Till Johannes; Nikendei, Christoph (PLOS ONE, 2018)
Objective Numerous studies from diverse contexts have confirmed high stress levels and stress-associated health impairment in medical students. This study aimed to explore the differential association of perceived stress with private and training-related stressors in medical students according to their stage of medical education.
Gesehen am 04.07.2019